2018
DOI: 10.18805/lr-3928
|View full text |Cite
|
Sign up to set email alerts
|

Studies on site specific nutrient management (SSNM) on growth and yield of groundnut (Arachis hypogaea) under irrigation in southern Karnatak

Abstract: A field experiment was conducted at the Main Research Station, University of Agricultural Sciences, Hebbal, Bangalore, to know the effect of site specific nutrient management (SSNM) on growth and yield of groundnut. The fertilizers were applied to the crop based on uptake pattern, target yield and soil fertility status. The study indicated that application of fertilizers based on SSNM for target yield of 2.5 t ha-1 + S (10 kg ha-1) + B (10 kg ha-1) + Zn (12.50 kg ha-1) recorded significantly higher growth par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Similar results were obtained by Gawai et al (2005) [9] studied that the residual effect of application of 100 per cent RDF and 5t FYM ha -1 to proceeding crop sorghum resulted in significantly higher grain and haulm yield of chickpea. These findings are also in line with those reported by Kuldeep et al (2018) [10] and Patil et al (2018) [14] , respectively. The similar interpretation was also reported by Ashoka et al (2008) [3] results revealed that residual effect of RDF (150:75:40kg N, P 2 O 5 , K 2 O ha -1 ) +25kg ZnSO 4 +10kg FeSO 4 +35kg Vermicompost to chickpea also increased pods per plant (100.33), test weight (24.80g) and seed yield (15.4q ha -1 ) over RDF alone and all other treatments.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained by Gawai et al (2005) [9] studied that the residual effect of application of 100 per cent RDF and 5t FYM ha -1 to proceeding crop sorghum resulted in significantly higher grain and haulm yield of chickpea. These findings are also in line with those reported by Kuldeep et al (2018) [10] and Patil et al (2018) [14] , respectively. The similar interpretation was also reported by Ashoka et al (2008) [3] results revealed that residual effect of RDF (150:75:40kg N, P 2 O 5 , K 2 O ha -1 ) +25kg ZnSO 4 +10kg FeSO 4 +35kg Vermicompost to chickpea also increased pods per plant (100.33), test weight (24.80g) and seed yield (15.4q ha -1 ) over RDF alone and all other treatments.…”
Section: Resultssupporting
confidence: 93%
“…However, numerically the highest values were noted in T 1 (N 43 p 43 K 50 ) and the lowest was in control. Similar results were also reported by Patil et al (2018) in groundnut. Different treatments significantly affected number of pods per plant (Table 1).…”
supporting
confidence: 91%
“…This might be due to higher yields at higher nutrient level. Hellal and Abdelhamid (2013), Patil et al (2018) and Billore and Srivastava (2015) reported similar results. Significantly higher B:C was observed in t 1 while the lowest was in control.…”
mentioning
confidence: 68%
“…Singh et al (2023) [6] conducted an experiment at 5 locations of Naugarh block of Chandauli, UP during Rabi season of 2019 to test the STCR model. Patil et al (2018) [4] took the supply factor into consideration for the prescription of different doses of fertilizer for various crops. Biradar et al (2012) [1] used a formula to estimate the fertilizer nutrients required to achieve the targeted yield through site specific nutrient management (SSNM) given as nutrients required for the crop = Target yield (q ha -1 ) × Nutrient removal by a crop (kg q -1 ).…”
Section: Review Of Literaturementioning
confidence: 99%